A potential new role for fungi in a wastewater MBR biological nitrogen reduction system. Issue 6 (1st November 2002) - Smith, Daniel W; Guest, R K
Abstract : The fastidious nature of nitrifying bacteria has caused many operational problems for wastewater treatment plants employing some form of biological nutrient removal. Research in the field has focused solely on meeting the requirements of this group of bacteria. Recently fungi have been recognized to perform denitrification at greater rates than bacteria. Combining fungi nitrification ability and resistance to inhibitory chemicals, there is the potential for development of a new fungi based biological nitrogen removal system. From the data reviewed, the system would have several significant advantages over conventional biological nutrient removal systems. This paper reviews the ability of fungi to carry out biological nitrogen removal and the potential performance of a fungi based system.